Additive valuations of streams of payoffs that satisfy the time value of money principle: characterization and robust optimization - Abraham Neyman (Theoretical Economics, 2023)
This paper characterizes those preferences over bounded infinite utility streams that satisfy the time value of money principle and an additivity property, and the subset of these preferences that in addition are either impatient or patient. Based on this characterization, the paper introduces a concept of optimization that is robust to a small imprecision in the specification of the preference, and proves that the set of feasible streams of payoffs of a finite Markov decision process admits such a robust optimization.
Keywords: C72; E43; 330; infinite streams of payoffs; robust optimization; utility; Valuations